Design and development of tapered slot antenna array - Zhang, Yingdi (2015)
This final year project is to make innovative design and development of tapered slot antenna elements of an array antenna for a low cost UWB radar system. Our aim is to design a taper slot antenna array element which is able to work under frequency range 1.5-4.5GHz at a return loss of 10dB. In addition, an antipodal Vivaldi antenna array is designed and fabricated beyond project scope to operate between 500MHz and 590MHz at a return loss of 10dB for further understanding. The simulated results of both two types of antennas are able to meet the requirements respectively. For the fabricated single element Tapered slot antenna, within the required frequency range of 1.5GHz to 4.5GHz, the return loss of the TSA is below -10dB at most of the time, except for some minor pimpling between frequency 1.5GHz to 2GHz. In this project, a virtual Tapered slot antenna array is built and tested for the Through-The-Wall Radar applications and the result shows that this virtual antenna array can detect the shape and position of the objects behind the wall clearly. For the fabricated single element of Antipodal Vivaldi antenna, the measurement results meet the design requirement well. This report sums all the work that have been done on the antennas design, including the literature review, design procedure, software simulations, integration of antenna array and final testing using network analyzer.